INVESTIGATION OF NaCl DELIQUESCENCE IN POROUS SUBSTRATES USING RH-XRD - Linnow K.; Juling H.; Steiger M. (My University, 2007)
We report on the use of X-ray diffractometry under controlled conditions of temperature and relative humidity (RH-XRD) for the investigation of NaCl deliquescence in the pore space of glass filter frits, which were used as model substrates. The study confirms that RH-XRD is an appropriate experimental technique for the in situ observation of phase transformation in porous materials. It is used for an investigation of both the deliquescence kinetics and the deliquescence humidity within pores of different median pore diameter. Several major influences affecting deliquescence rates in the pore space close to the surface of a porous material are discussed. It appears that quite short-term variation of ambient relative humidity, e.g., typical daily fluctuations, might induce damaging deliquescence–crystallization cycles within the pore space of building materials. In agreement with theoretical considerations it was found that confinement of NaCl crystals in pores with median diameters in the range 1.4–70 μm does not affect the deliquescence humidity of the salt.
Keywords: BUILDING DETERIORATION; STONE DECAY; DELIQUESCENCE; SODIUM CHLORIDE; X-RAY DIFFRACTION; KINETICS